2021
DOI: 10.4103/jehp.jehp_988_20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early clinical exposure in medical education

Abstract: Early clinical exposure (ECE) is a teaching-learning methodology which fosters the exposure of medical students to the patients as early as the first year of medical college. A worldwide number of research studies investigated the outcome of ECE and found, ECE sessions motivate the medical student in various ways making their academic strength, improve clinical skills, and improve communication skills and making them more confident. In the medical curriculum, ECE makes an overall impact on student's performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“… 5 It has been found that early clinical exposure motivates the students in various ways, increasing their academic strength and improving clinical skills. 6 From wards, outpatient department to neonatal intensive care unit, operation theatre and Emergency we observed, practised, and learnt the fundamental concepts, moral attitudes, communication skills and empathy.…”
Section: Experiencementioning
confidence: 99%
“… 5 It has been found that early clinical exposure motivates the students in various ways, increasing their academic strength and improving clinical skills. 6 From wards, outpatient department to neonatal intensive care unit, operation theatre and Emergency we observed, practised, and learnt the fundamental concepts, moral attitudes, communication skills and empathy.…”
Section: Experiencementioning
confidence: 99%
“… 1 If medical students wish to pursue such a competitive specialty, they need early exposure to make an informed choice to commit themselves. 2 3 In the United Kingdom, aspiring neurosurgeons must demonstrate a rich portfolio of extracurricular achievements to highlight dedication and insight into the specialty. 4 Often, the achievements required to secure a neurosurgical training position take several years.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Meanwhile, clinical classes encourage medical students in a variety of ways, including their academic performance, clinical competency, communication abilities, and self-assurance. 2 Due to the ongoing scientific revolution in medicine, it is imperative that MBBS graduates need to have a solid foundation in the basic sciences and through clinical experiences, students can put their learning to use and pick up new abilities under the supervision of a preceptor. 3 The basics and clinical are two essential components of the MBBS curriculum, and as we progress from the basics to the clinical, there is a change in study subjects, as well as how we feel and what we experience as medical students.…”
Section: Introductionmentioning
confidence: 99%